Testicular volume and semen characteristics in the endangered southern muriqui (Brachyteles arachnoides) - Arakaki, Paloma Rocha; Borges Salgado, Paula Andrea; Friciello Teixeira, Rodrigo Hidalgo [UNESP]; Rassy, Fabricio Braga; Barros Vaz Guimaraes, Marcelo Alcindo de; Valle, Rodrigo del Rio do (Wiley-Blackwell, 2019)
Background The southern muriqui (Brachyteles arachnoides) is an endangered Neotropical primate. Semen collection and description of its traits, as well as testicular morphometry, have never been reported for this species. Methods Testicles from five healthy adult captive southern muriqui were measured, and semen was collected by rectal probe electrostimulation (RPE). Results and Conclusions A solid coagulum was identified in all ejaculates, and none of them liquefied, spontaneously or non-spontaneously. It was possible to collect semen using RPE, and although solids coagula did not liquefy, we managed to describe ejaculates characteristics and also confirmed that southern muriqui have relatively large testes size. Further investigations are needed to improve coagulum handling, to achieve a better spermatozoa recovery aiming its application in assisted reproductive technologies.
Keywords: primate reproduction; rectal electrostimulation; semen evaluation; seminal coagulum; vulnerable species